Overexpression of miRNA-221 promotes cell proliferation by targeting the apoptotic protease activating factor-1 and indicates a poor prognosis in ovarian cancer - Li, Jie; Li, Qiang; Huang, He; Li, Yinguang; Li, Li; Hou, Wenhui; You, Zeshan (International journal of oncology, 2017)
MicroRNAs are a class of small non-coding, endogenous RNAs involved in cancer development and progression. MicroRNA-221 (mir-221) has been reported to have both an oncogenic and tumor-suppressive role in human tumors, but the role of miR-221 in ovarian cancer is poorly understood. In the present study, the expression levels of miR-221 and the apoptosis protease activating factor 1 (APAF1) protein in 63 samples of ovarian cancer tissues and the cell lines, IOSE25, A2780, OVCAR3, SKOV3 and 3AO were detected by quantitative reverse-transcription polymerase chain reaction (qRT-PCR) and western blot analysis, respectively. Cell proliferation was measured using cell counting kit-8 (CCK-8); cell migration and invasion were detected using a transwell assay; cell apoptosis was evaluated by flow cytometry and hoechst staining, and a luciferase assay was performed to verify a putative target site of miR-221 in the 3'-UTR of APAF1 mRNA. Expression of miR-221 was upregulated in ovarian cancer tissues. Patients with increased miR-221 expression levels had a reduced disease-free survival (P=0.0014) and overall survival (P=0.0058) compared with those with low miR-221 expression. Transfection of SKOV3 and A2780 cell lines with miR-221 inhibitor induced APAF1 protein expression, suppressed cell proliferation and migration and promoted tumor cell apoptosis. In conclusion, the APAF1 gene was confirmed as a direct target of miR-221 and overexpression of APAF1 suppressed ovarian cancer cell proliferation and induced cell apoptosis in vitro. These findings indicate that miR-221-APAF1 should be studied further as a potential new diagnostic or prognostic biomarker for ovarian cancer.